CD4+ cell count and outcomes among HIV-infected compared with uninfected medical ICU survivors in a national cohort. (15th November 2021) - Akgün, Kathleen M.; Krishnan, Supriya; Butt, Adeel A.; Gibert, Cynthia L.; Graber, Christopher J.; Huang, Laurence; Pisani, Margaret A.; Rodriguez-Barradas, Maria C.; Hoo, Guy W. Soo; Justice, Amy C.; Crothers, Kristina; Tate, Janet P.
Abstract : Background: People with HIV (PWH) with access to antiretroviral therapy (ART) experience excess morbidity and mortality compared with uninfected patients, particularly those with persistent viremia and without CD4 + cell recovery. We compared outcomes for medical intensive care unit (MICU) survivors with unsuppressed (>500 copies/ml) and suppressed (⩽500 copies/ml) HIV-1 RNA and HIV-uninfected survivors, adjusting for CD4 + cell count. Setting: We studied 4537 PWH [unsuppressed = 38%; suppressed = 62%; 72% Veterans Affairs-based (VA) and 10 531 (64% VA) uninfected Veterans who survived MICU admission after entering the Veterans Aging Cohort Study (VACS) between fiscal years 2001 and 2015. Methods: Primary outcomes were all-cause 30-day and 6-month readmission and mortality, adjusted for demographics, CD4 + cell category (≥350 (reference); 200–349; 50–199; <50), comorbidity and prior healthcare utilization using proportional hazards models. We also adjusted for severity of illness using discharge VACS Index (VI) 2.0 among VA-based survivors. Results: In adjusted models, CD4 + categories <350 cells/μl were associated with increased risk for both outcomes up to 6 months, and risk increased with lower CD4 + categories (e.g. 6-month mortality CD4 + 200–349 hazard ratio [HR] = 1.35 [1.12–1.63]; CD4 + <50 HR = 2.14 [1.72–2.66]); unsuppressed status was not associated with outcomes. After adjusting for VI in models stratified by HIV, VI quintiles were strongly associated with both outcomes at both time points. Conclusion: PWH who survive MICU admissions are at increased risk for worse outcomes compared with uninfected, especially those without CD4 + cell recovery. Severity of illness at discharge is the strongest predictor for outcomes regardless of HIV status. Strategies including intensive case management for HIV-specific and general organ dysfunction may improve outcomes for MICU survivors. Abstract : Supplemental Digital Content is available in the text